EVALUACIÓN DE LA RESISTENCIA A LA CORROSIÓN DE ALEACIONES DENTALES COBRE ALUMINIO NPG Y NPG+2 EN SALIVA ARTIFICIAL USANDO MÉTODOS ELECTROQUÍMICOS - Quezada y Cols., Elvar (2019)
The present work include the determination of microstructures of copper-aluminum dental alloys NPG and NPG+2, and the plot of their respective potenciodynamical polarization curves in artificial saliva. Based in these curves, densities of corrosion currents were determined by Tafel method, values that were used to calculate alloy dissolution velocity, it was encountered NPG+2 alloy is the most susceptible to corrosion. Also, corrosion products have been analyzed by EDAX, obtaining as result that in the most cases ions of Cu and Al were liberated to electrolytic environment, and in the minority of cases ions el Zn, Fe and Ni. This behavior affects health of patients with dental prosthesis.